2016
DOI: 10.3389/fpsyt.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin for Male Subjects with Autism Spectrum Disorder and Comorbid Intellectual Disabilities: A Randomized Pilot Study

Abstract: Approximately half of autism spectrum disorder (ASD) individuals suffer from comorbid intellectual disabilities (IDs). Oxytocin (OXT) receptors are highly expressed in temporal lobe structures and are likely to play a modulatory role in excitatory/inhibitory balance, at least based on animal model findings. Thus, it is feasible that in the highly representative group of Kanner-type ASD subjects, OXT could have a beneficial effect on social communication and social interaction. The aim of this pilot study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 61 publications
1
71
1
1
Order By: Relevance
“…Only Yatawara et al and Munesue et al reported severe adverse events. In all, two of these occurred in the placebo group, and three in the oxytocin group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only Yatawara et al and Munesue et al reported severe adverse events. In all, two of these occurred in the placebo group, and three in the oxytocin group.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it was decided that data from both phases of the crossover trials would be used regardless of the length of the washout periods. A detailed description of the included studies can be found in Table …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that OT can be used for the treatment of social avoidance in psychological disorders. Furthermore, whether we can extend the results obtained in the mouse to human behavioral recovery is of interest, especially since there have been reports regarding the effectiveness of OT for impaired social interaction in cases of autism spectrum disorder (ASD) [5355]. …”
Section: Discussionmentioning
confidence: 99%
“…However, evidence from OXT treatment trials in ASD patients is more equivocal: Several studies have reported that OXT administration improves social abilities in individuals with ASD (19,20), but others have found no improvement in the trial's primary outcome measure (21)(22)(23)(24). Interestingly, many OXT administration studies have documented significant Significance Autism spectrum disorder (ASD) is characterized by social deficits.…”
mentioning
confidence: 99%